Does neoadjuvant chemotherapy regimen affect sarcopenia status in patients with breast cancer?. (December 2022) - Jang, Min Kyeong; Park, Seho; Park, Chang; Doorenbos, Ardith Z.; Go, Jieon; Kim, Sue
Abstract: Background: Low muscle mass, or sarcopenia, predicts poorer treatment outcomes in breast cancer. Neoadjuvant chemotherapy is the main treatment to improve surgical outcomes for breast cancer, yet few studies have assessed the relationships between different chemotherapy regimens and sarcopenia. This study compared body composition change between two neoadjuvant chemotherapy regimens: AC-T (anthracyclines and cyclophosphamide followed by a taxane) and TCHP (docetaxel, carboplatin, trastuzumab, and pertuzumab). Methods: This study included 298 patients with breast cancer who received neoadjuvant chemotherapy between 2017 and 2020 at one university hospital. Body composition was assessed by computed tomography. Multiple linear regression was performed to examine predictors of SMI change. Results: Patients receiving TCHP showed a significant mean skeletal muscle index (SMI) decrease of 1.6 cm 2 /m 2 (SD = 3.5, p  < .001); patients receiving AC-T showed no significant change in mean SMI. The TCHP group also showed significantly decreased visceral and subcutaneous fat mass, while the AC-T group showed increases in both. The TCHP group had significantly more patients with newly diagnosed sarcopenia after neoadjuvant chemotherapy than the AC-T group (12% vs 1%, respectively). Chemotherapy regimen was the only significant predictor of muscle mass loss, and the TCHP group's mean SMI decrease was 3.124 greater than that of the AC-T group (p = .015). Conclusions: Patients receiving TCHP have a higher risk of muscle mass loss than those receiving AC-T. Considering the severe SMI decline observed in the TCHP group, further prospective studies are called for to examine treatment-induced sarcopenia and its relationship to body composition. Highlights: Type of chemotherapy regimen is an important predictor of muscle mass loss during neoadjuvant chemotherapy in patients with breast cancer. Patients receiving the TCHP regimen as neoadjuvant chemotherapy showed a higher risk of muscle mass loss than those receiving the AC-T regimen. After neoadjuvant chemotherapy, patients who received the TCHP regimen had significantly higher risk of newly diagnosed sarcopenia than those who received the AC-T regimen. Further prospective studies are called for to examine treatment-induced sarcopenia and its relationship to body composition.